On Cartan torsion of 4-dimensional Finsler manifolds - Akbar Tayebi (Journal of Hyperstructures, 2024)
There are several non-Riemannian curvatures in Finsler geometry which show the complexity of Finsler geometry with respect to Riemannian geometry. Amon these quantities, the Cartan and mean Cartan torsion have very important and brilliant positions. In this paper, we find the necessary and sufficient condition under which a 4-dimensional Finsler manifold is C-reducible. Also, we find the necessary and sufficient condition under which a 4-dimensional Finsler manifold has vanishing ${\bar I}$-curvature.